2017
DOI: 10.1111/cdev.12822
|View full text |Cite
|
Sign up to set email alerts
|

Technoference: Parent Distraction With Technology and Associations With Child Behavior Problems

Abstract: Heavy parent digital technology use has been associated with suboptimal parent-child interactions, but no studies examine associations with child behavior. This study investigates whether parental problematic technology use is associated with technology-based interruptions in parent-child interactions, termed "technoference," and whether technoference is associated with child behavior problems. Parent reports from 170 U.S. families (child M = 3.04 years) and actor-partner interdependence modeling showed that m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
251
4
17

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 351 publications
(319 citation statements)
references
References 55 publications
15
251
4
17
Order By: Relevance
“…Now that ecological factors have been found associated with weaker transmission of autonomous representations to secure attachment, the mechanisms responsible for these constraints need to be identified and understood, for example, by testing whether family stress mediates this moderator effect (Conger et al., ) and in addition, what predicts child attachment (in)security in at‐risk samples if not parental attachment representations. Also, given the potential implications of amount of time as facilitating transmission of autonomous as well as nonautonomous attachment, studies need to move beyond proxy variables and with help of ambulatory assessment index actual time in interaction as this variable may be determined by many factors, including aging, parental role divisions, and competing activities (e.g., McDaniel & Radesky, ). The current study also demonstrates the viability of IPD meta‐analysis to answer questions in the field of attachment to address theoretical issues and to build models that capture small but (through their cumulative nature) important effects.…”
Section: Discussionmentioning
confidence: 99%
“…Now that ecological factors have been found associated with weaker transmission of autonomous representations to secure attachment, the mechanisms responsible for these constraints need to be identified and understood, for example, by testing whether family stress mediates this moderator effect (Conger et al., ) and in addition, what predicts child attachment (in)security in at‐risk samples if not parental attachment representations. Also, given the potential implications of amount of time as facilitating transmission of autonomous as well as nonautonomous attachment, studies need to move beyond proxy variables and with help of ambulatory assessment index actual time in interaction as this variable may be determined by many factors, including aging, parental role divisions, and competing activities (e.g., McDaniel & Radesky, ). The current study also demonstrates the viability of IPD meta‐analysis to answer questions in the field of attachment to address theoretical issues and to build models that capture small but (through their cumulative nature) important effects.…”
Section: Discussionmentioning
confidence: 99%
“…Not only is distraction linked with parenting behaviors, but it is also linked with family interactions and relationship quality. Researchers in the literature on technoference —or the everyday intrusions and interruptions of devices in our face‐to‐face interactions (McDaniel & Coyne, )—have found that parents perceive technology interruptions happening in their interactions with their romantic partners, with their children, and in their parenting and coparenting interactions (McDaniel & Coyne, , ; McDaniel, Galovan, Cravens, & Drouin, ; McDaniel & Radesky, , ). Not only are these interruptions happening, but more frequent interruptions are connected with perceptions of lower quality couple and coparenting relationships.…”
Section: How Does This Use Impact Parents and Parenting?mentioning
confidence: 99%
“…For example, in interviews some parents talked about noticing that their children are less relaxed, more upset, or unsatisfied when the parent is using a device (Radesky et al, ), with some children and teens actively trying to get the parent to put the phone away (Oduor et al, ; Sharaievska & Stodolska, ). In studies of young children, parents perceive greater problem behaviors, such as externalizing (e.g., acting out, anger) and internalizing (e.g., withdrawal, sulking), when more technological interruptions occur in their interactions with their children (McDaniel & Radesky, , ). Parents also perceive child behavior to be more difficult on days when parent device use is more problematic and absorbing (McDaniel & Radesky, ).…”
Section: How Does Parent Phone Use Impact Children?mentioning
confidence: 99%
See 2 more Smart Citations